2010
DOI: 10.1177/0193945910385363
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness-Based Stress Reduction (MBSR) on Health Among Breast Cancer Survivors

Abstract: The purpose of this study was to examine the effects of a MBSR program on physiological and psychological outcomes among early-stage breast cancer survivors. A quasi-experimental, pre-and posttest control group design was selected. The intervention group received the MBSR intervention. The control group received no MBSR intervention. ANOVA and ANCOVA were used to analyze data. The intervention group demonstrated statistically significant improvement in physiological and psychological outcomes including reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
100
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 44 publications
(68 reference statements)
7
100
1
4
Order By: Relevance
“…These pilot results are consistent with previous studies that examined the effectiveness of mindfulness-based interventions. Although this study was undertaken in a different study population, it supports previous studies that show that mindfulness-based interventions result in reductions in blood pressure readings in samples of breast cancer survivors, 5 type II diabetics, 6 and breast and prostate cancer patients. 7 In addition, our pilot results show that the mindfulness-based ELDERSHINE program is feasible to implement in a low-income housing residence center that serves older adults.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…These pilot results are consistent with previous studies that examined the effectiveness of mindfulness-based interventions. Although this study was undertaken in a different study population, it supports previous studies that show that mindfulness-based interventions result in reductions in blood pressure readings in samples of breast cancer survivors, 5 type II diabetics, 6 and breast and prostate cancer patients. 7 In addition, our pilot results show that the mindfulness-based ELDERSHINE program is feasible to implement in a low-income housing residence center that serves older adults.…”
Section: Discussionsupporting
confidence: 84%
“…This paper reports the pilot study of just such an intervention. Currently, there is evidence to suggest that mindfulness meditation can lower blood pressure; [5][6][7] therefore, we elected the implementation of a mindfulness-based program in a Baltimore City senior housing facility. Rooted in Buddhist tradition and formally developed by Jon Kabat-Zinn 8 in 1979, mindfulness-based stress reduction (MBSR) programs are founded upon an active awareness of physical and mental states and teach participants to concentrate on breathing, and to relax their minds and bodies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kraft & Pressman (2012) Induced smiling in an experiment led to quicker heart rate recovery after stress inductions. Matchim et al (2011) A mindfulness intervention reduced heart rate, blood pressure, and respiratory rate, but lower waking cortisol was not sustained over time. Ostir et al (2006) Positive emotions were related to lower levels of both types of blood pressure for people not on hypertensive medications, but only to lower diastolic blood pressure for those on these medications.…”
Section: Yanek Et Al (2013)mentioning
confidence: 94%
“…Seven full-text articles were assessed for eligibility. One article had to be excluded because the study it reported was not randomized 27 . The remaining six articles reported results from three rcts.…”
Section: Study Selectionmentioning
confidence: 99%